2016
DOI: 10.12659/msm.900610
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality-of-Life and Functional Outcomes in Short-Stem Versus Standard-Stem Total Hip Arthroplasty: An 18-Month Follow-Up Cohort Study

Abstract: BackgroundOsteoarthritis (OA) progressively produces symptoms and disability that may significantly reduce health-related quality of life (HRQoL). Total hip arthroplasty (THA) is an important treatment for symptomatic OA. An alternative to standard-stem THA for younger patients is short-stem THA. The aim of this study was to investigate potential HRQoL and functional outcome differences between these patient groups to provide additional data that will be clinically useful in the decision making between the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, the difference in the quality of life after shortstem and standard-stem hip arthroplasty has already been reviewed in several studies that suggest similar functional outcome with slight benefit for short stem prosthesis in younger patients due to faster post-operative recovery as well as less stress shielding [9,10,24,25]. A supplement reduction of thigh pain using short-stem hip arthroplasty might has an effect on sleep improvement, but existing studies show no significant difference compared with conventional standardstem hip arthroplasty [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the difference in the quality of life after shortstem and standard-stem hip arthroplasty has already been reviewed in several studies that suggest similar functional outcome with slight benefit for short stem prosthesis in younger patients due to faster post-operative recovery as well as less stress shielding [9,10,24,25]. A supplement reduction of thigh pain using short-stem hip arthroplasty might has an effect on sleep improvement, but existing studies show no significant difference compared with conventional standardstem hip arthroplasty [26].…”
Section: Discussionmentioning
confidence: 99%
“…The current gold standard for hip osteoarthrosis is a total hip replacement [8]. For younger patients with hip osteoarthrosis, the short-stem hip prosthesis is a new method that promises reduced surgical trauma as well as faster post-operative recovery compared with standard-stem prosthesis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…4 While one study comparing mediumterm PROs between a different neck-preserving, short-stem implant, and a neck-sacrificing implant reported that there was no significant difference in QOL scores, it still advocated the use of the NPS stem implant in younger patients as it allows for a less-invasive technique and facilitates future revision. 38 A limitation of this study is the low level of evidence, as this was a nonrandomized and nonblinded cohort study. However, the findings observed are promising and serve as a basis for potential future randomized controlled trials.…”
Section: Discussionmentioning
confidence: 95%
“…The categories of health tested included physical functioning (PF), role limitations due to physical health problems (RP), bodily pain (BP), general health perceptions (GH), vitality (VT), social functioning (SF), role limitations due to emotional problems (RE), and general mental health (MH) [12][13][14].…”
Section: Sf-36mentioning
confidence: 99%